The effects of ginger intake on weight loss and metabolic profiles among overweight and obese subjects: A systematic review and meta-analysis of randomized controlled trials - Maharlouei, Najmeh; Tabrizi, Reza; Lankarani, Kamran B.; Rezaianzadeh, Abbas; Akbari, Maryam; Kolahdooz, Fariba; Rahimi, Maryam; Keneshlou, Fariba; Asemi, Zatollah (Critical reviews in food science and nutrition, 2019)
This systematic review and meta-analysis of randomized controlled trials (RCTs) was performed to summarize the effect of ginger intake on weight loss, glycemic control and lipid profiles among overweight and obese subjects. We searched the following databases through November 2017: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The relevant data were extracted and assessed for quality of the studies according to the Cochrane risk of bias tool. Data were pooled using the inverse variance method and expressed as Standardized Mean Difference (SMD) with 95% Confidence Intervals (95% CI). Heterogeneity between studies was assessed by the Cochran Q statistic and I-squared tests (I 2 ). Overall, 14 studies were included in the meta-analyses. Fourteen RCTs with 473 subjects were included in our meta-analysis. The results indicated that the supplementation with ginger significantly decreased body weight (BW) (SMD −0.66; 95% CI, −1.31, −0.01; P = 0.04), waist-to-hip ratio (WHR) (SMD −0.49; 95% CI, −0.82, −0.17; P = 0.003), hip ratio (HR) (SMD −0.42; 95% CI, −0.77, −0.08; P = 0.01), fasting glucose (SMD −0.68; 95% CI, −1.23, −0.05; P = 0.03) and insulin resistance index (HOMA-IR) (SMD −1.67; 95% CI, −2.86, −0.48; P = 0.006), and significantly increased HDL-cholesterol levels (SMD 0.40; 95% CI, 0.10, 0.70; P = 0.009). We found no detrimental effect of ginger on body mass index (BMI) (SMD −0.65; 95% CI, −1.36, 0.06; P = 0.074), insulin (SMD −0.54; 95% CI, −1.43, 0.35; P = 0.23), triglycerides (SMD −0.27; 95% CI, −0.71, 0.18; P = 0.24), total- (SMD −0.20; 95% CI, −0.58, 0.18; P = 0.30) and LDL-cholesterol (SMD −0.13; 95% CI, −0.51, 0.24; P = 0.48). Overall, the current meta-analysis demonstrated that ginger intake reduced BW, WHR, HR, fasting glucose and HOMA-IR, and increased HDL-cholesterol, but did not affect insulin, BMI, triglycerides, total- and LDL-cholesterol levels.